2015
DOI: 10.1002/bit.25835
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling activity of enzyme‐functionalized silica nanobeads

Abstract: The amelioration of biofouling in industrial processing equipment is critical for performance and reliability. While conventional biocides are effective in biofouling control, they are potentially hazardous to the environment and in some cases corrosive to materials. Enzymatic approaches have been shown to be effective and can overcome the disadvantages of traditional biocides, however they are typically uneconomic for routine biofouling control. The aim of this study was to design a robust and reusable enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Synthesis of silica NPs was based on the Stöber method 55 and the subsequent functionalisation steps (amination, carboxylation) were carried out according to a procedure previously described. 56 For the synthesis of curc-NPs, 80 mg of carboxylatefunctionalised silica NPs, 47 mg of DCC, 14 mg of DMAP and 80 mg of curcumin were dispersed in 50 mL of dry DMF under inert atmosphere at 0 C. The mixture was stirred to room temperature and then le under agitation for 20 h. Yellowish coloured curc-NPs were recovered by centrifugation (9000 rpm, 20 min) and washed at least three times with water via centrifugation (Scheme 1). In the case where uorescently labelled NPs were desired, 1 mL of dye conjugate was added in the mixture of the adapted Stoeber reaction method.…”
Section: Nanoparticle Synthesismentioning
confidence: 99%
“…Synthesis of silica NPs was based on the Stöber method 55 and the subsequent functionalisation steps (amination, carboxylation) were carried out according to a procedure previously described. 56 For the synthesis of curc-NPs, 80 mg of carboxylatefunctionalised silica NPs, 47 mg of DCC, 14 mg of DMAP and 80 mg of curcumin were dispersed in 50 mL of dry DMF under inert atmosphere at 0 C. The mixture was stirred to room temperature and then le under agitation for 20 h. Yellowish coloured curc-NPs were recovered by centrifugation (9000 rpm, 20 min) and washed at least three times with water via centrifugation (Scheme 1). In the case where uorescently labelled NPs were desired, 1 mL of dye conjugate was added in the mixture of the adapted Stoeber reaction method.…”
Section: Nanoparticle Synthesismentioning
confidence: 99%
“…Most of the nanobeads used so far are being separated based on size exclusion. For instance, in the work of Zanoni et al, 21 a 500 nm Si-nanobeads with immobilized enzyme that was used to distract biolm growth were recovered using 0.45 mm lters. However, due to the presence of residual gels that could not be isolated from the Si-nanobeads using a mere ltration, the recycled Si-nanobeads exhibited reduced mechanical or enzymatic activity on the biolms.…”
Section: Performance Comparison Between Lab-made and Commercial Np Spmentioning
confidence: 99%
“…As a result, authors suggested the need to develop an alternative and highly efficient recovery and cleaning methodology. 21 In this work, these challenges are resolved by using magneto-responsive nanobeads.…”
Section: Performance Comparison Between Lab-made and Commercial Np Spmentioning
confidence: 99%
“…Lequette et al (2010) combined seven proteases and polysaccharidases with CIP strategies against Pseudomonas fluorescens and Bacillus cereus biofilms. More recently, Zanoni, Habimana, Amadio, and Casey (2015) attempted to control P. fluorescens biofilms with Proteinase K immobilized on silica nanobeads. Meshram, Dave, Joshi, Dharani, Kirubagaran, and Venugopalan (2016) studied P. aeruginosa biofilm control by immobilizing alginate lyase on cellulose acetate membranes.…”
Section: Introductionmentioning
confidence: 99%